Evaluation of Marigold Varieties Under Minimum Tillage Condition in Terai Region of Nepal (Far Western Review, 2025)
A field research was conducted at Kishannagar, Bardibas-06, Mahottari, Nepal for the study of the growth and yield performance of marigold varieties of African marigold (Tagetes erecta L.) under minimum tillage in Terai region of Nepal. This research has been conducted under RCBD (randomized complete block design) consists of three varieties (Pusa Basanti, Duo Orange & Navarangi) and seven replications. Various growth and yield parameters were considered. The data were analyzed by Genstat ver. 2015. The data analyzed from the research highlighted that all growth and yield characteristics were profoundly affected by the different varieties. The results demonstrated that varietal differences significantly influenced all measured traits. Among the three varieties, Navarangi consistently outperformed the others. It recorded the highest number of primary branches (28), followed closely by Pusa Basanti (27), while Duo Orange had the lowest (13). A similar trend was observed in the number of secondary branches, with Navarangi registering the highest count (87), Pusa Basanti showing intermediate performance (60.7), and Duo Orange again ranking lowest. Regarding petiole length, Navarangi (6.40 cm) and Duo Orange (6.37 cm) exhibited comparable and longer petioles, whereas Pusa Basanti had the shortest (4.88 cm). In terms of yield, Navarangi achieved the highest harvest weight (519 g), followed by Duo Orange (376 g) and Pusa Basanti (319 g). Among the varieties studied, Navarangi emerged as superior in terms of growth and yield characteristics under minimum tillage conditions. Consequently, it is essential that this experiment be replicated in farmers’ fields for validation, and an evaluation of customer preferences should also be conducted.